(untitled) (Proceeding of SINERGY, 2026)
Indonesia’s commitment to the Paris Agreement, as outlined in its Enhanced Nationally Determined Contribution (ENDC), mandates the transparent and accurate reporting of Greenhouse Gas (GHG) emissions. However, a critical gap persists between official administrative data and ecological reality. The 2025 hydrometeorological disasters in Sumatra, which were marked by the presence of massive drifting logs during flash floods, revealed significant discrepancies in deforestation reporting. This research analyzes the legal implications of these data disparities regarding Indonesia’s State Responsibility and explores the conceptualization of an Independent Digital Auditor based on the Albanian Government’s AI governance model, known as Diella. Using normative legal research with a comparative and statutory approach, this study finds that inaccurate GHG reporting constitutes a breach of the due diligence principle and transparency obligations under international law. Such discrepancies prevent effective climate resilience planning and may trigger State Responsibility for administrative omissions. To address this, the research proposes adopting the Albanian Diella model as a radical technological intervention. This AI mechanism integrates Big Data and real-time satellite imagery through Difference Imaging, which is a technique adapted from astrophysical surveys, to instantly isolate physical alterations in land cover by comparing reference and new imagery. By utilizing Convolutional Neural Networks (CNN) for advanced feature extraction, the AI can detect illegal logging patterns invisible to manual monitoring. Furthermore, the system acts as a surrogate model, reducing the computational time required to audit complex carbon flows to milliseconds while maintaining high precision. The study concludes that while AI acts as a radical transparency tool to restore the integrity of national reports, it must operate under a Human-Guided AI (HG-AI) framework. This framework ensures that while AI provides unalterable technical evidence, final policy decisions and legal enforcement remain with state authorities to uphold constitutional values and social justice. This synergy between law and technology is key to transforming public administration into an accountable and resilient system in the face of global climate change.